Effect of preconditioning to the soil environment on the performance of 20 cyanobacterial strains used as inoculum for biocrust restoration. (6th November 2019) - Giraldo‐Silva, Ana; Nelson, Corey; Penfold, Cory; Barger, Nichole N.; Garcia‐Pichel, Ferran
Abstract : Biological soil crusts are complex communities of organisms that develop on the top layer of dryland soils where they enhance important ecosystem services, including soil fertility and protection from erosion. Regrettably, a range of human activities such as cattle grazing, off‐road driving, hiking, and global warming result in significant deterioration of biocrust cover and their associated services. This scenario has prompted efforts to develop effective biocrust restoration strategies, which often involve the production of biocrust inoculum, both in greenhouse and in laboratory settings. Sometimes this inoculum is preconditioned in a process of "hardening" at considerable expense and effort in order to improve its fitness under harsh field conditions. But the positive effects of such hardening procedures have yet to be rigorously demonstrated. Here, we compared the growth performance of 20 cultured strains of biocrust cyanobacteria in outdoor tests on native soils as a function of preconditioning regimes consisting of increasingly high exposure to solar radiation, temperature and illumination daily variability, and recurrent wet‐dry cycles. Preconditioning improved performance in 13 out of 20 strains, particularly among pioneer crust‐forming Microcoleus spp. (eight out of eight). Improvements were variable among heterocystous strains (three out of four Scytonema spp., two out of four Tolypothrix spp., and none out of four Nostoc spp.). Based on these results, we recommend the inclusion of preconditioning treatments to increase inoculum survival rate and speed of cyanobacterial biocrust recovery in restoration of dryland soils.